Neuraxial Anesthesia in the Geriatric Patient - Sivevski, Atanas G.; Karadjova, Dafina; Ivanov, Emilija; Kartalov, Andrijan (Frontiers in Medicine, 2018)
Neuraxial anesthesia is recommended as a well-accepted option to minimize the perioperative side effects in the geriatric patients. The available data from the current researches have shifted the focus from the conventional approach to spinal anesthesia to the concept of low dose local anesthetic combined with opioids. What remains clear from all these studies is that hemodynamic stability is much better in patients who received low-doses of intrathecal bupivacaine in combination with opioids, which is possibly result of a potent synergistic nociceptive analgesic effect and their minimal potential effects on sympathetic pathways thus minimizing spinal hypotension. Spinal anesthesia with 5–10 mg of 0.5% heavy bupivacaine, fentanyl 20 mcg and 100 mcg of long-acting morphine added to the perioperative plan decreased the incidence of spinal hypotension and improved perioperative outcomes in the geriatric patients undergoing (low segment) surgical procedures. These findings may be of interest in the gynecologic geriatric surgery also in which area there are very few studies concerning the use of low-dose concept.